2005
DOI: 10.1158/1078-0432.ccr-04-2302
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Limit the Effectiveness of Herpes Simplex Virus Type 1 for Treatment of Oral Cancer in Mice

Abstract: Although the growth of experimental oral cancers can be inhibited by infection with the herpes simplex virus type 1 (HSV-1), the effect is incomplete. To define factors that might limit the effectiveness of the virus, we examined the roles of the innate immune system and the replication status of the tumor cells. AT-84 tumors were induced in strains of mice that had specific immune defects and were treated with the virus. Explanted tumors and tumor cells in culture were also infected. No differences in viral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The different response rates of cancer cell lines to oncolytic viruses seem to be dependent on rates of cell proliferation and the cell phase during infection13, 36. Rapidly dividing cells, which presumably express higher levels of ribonucleotide reductase, may serve as more suitable hosts for G207 replication37–40.…”
Section: Discussionmentioning
confidence: 99%
“…The different response rates of cancer cell lines to oncolytic viruses seem to be dependent on rates of cell proliferation and the cell phase during infection13, 36. Rapidly dividing cells, which presumably express higher levels of ribonucleotide reductase, may serve as more suitable hosts for G207 replication37–40.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its toxicity to cancer cells, some authors have utilised attenuated forms of the herpes simplex virus in the treatment of OSCC, which was shown in mouse models to inhibit the growth of oral cancer cells [178]. However, there are several limitations to this form of cancer therapy-primarily the elimination of the virus from the cancer cells and the inhibition of the virus by the immune system [179].…”
Section: Human Papilloma Virus Epstein-barr Virus and Herpes Simplexmentioning
confidence: 99%
“…Since NK cells possess both antiviral and antitumor properties, it is not surprising that their involvement is equally controversial. While there are examples of studies that have found no involvement of NK cells in response to oncolytic viral infections [58, 59], the majority of studies find that they are relevant in some capacity. To start, we will focus on studies that both highlight the need of achieving antitumor immunity and determine the essential role of NK cells in mediating this response.…”
Section: The Interface Between Nk Cells and Oncolytic Viral Therapymentioning
confidence: 99%